The Influence of Workload, Work-Life Balance, TQM on Work Effectiveness in Company "X" in Sidoarjo - Agustina, Ratna; Ashriana, Ahfi Nova; Sabani, Nurus; Mubarok, Ahmad (International Journal of Integrative Sciences, 2024)
This test aims to find out how much influence Workload, Work-Life Balance, and Total Quality Management have on work effectiveness. The research was conducted on 95 employees of PT. X in Sidoarjo. The type of data used in this research is primary data in the form of interviews and questionnaires. The data analysis carried out in this research used quantitative methods so that the data in the form of numbers was processed using statistical methods in the SPSS 23 program. The test results stated that each Workload, Work-Life Balance, and Total Quality Management variable significantly influenced Work Effectiveness.  Then, this research shows that the impact of workload variables, work-life balance, and total quality management simultaneously significantly influences the work effectiveness variable